A local product-of-exponentials method for the kinematic calibration of modular reconfigurable robots - Tan, Chee Tat. (2008)
A modular reconfigurable robot system is a collection of standardized individual link and joint components that can be assembled into a particular geometry for a specific task. However, kinematic calibration is necessary for such a system because machining tolerances in fabrication, assembly errors, wear, and drifts will create kinematic errors in the modular robot structure. Kinematic calibration is a process to identify and compensate for these inherent errors, through model modification, and thus can improve the absolute positioning accuracy of the robot. Similarly when applied for industrial robotics, kinematic calibration serves as a tool for improving the robot accuracy to its system repeatability. This thesis emphasizes on both the theoretical and experimental aspects of robot kinematic calibration.